TEACHING SPEAKING BY USING ARTIFICIAL INTELLIGENCE (AI)-BASED APPLICATION - Dimas Vega Rizqyqa Putra Budiyono; Mohammad Romadhoni (STKIP AL HIKMAH SURABAYA, 2024)
This study explores the implementation of the Speechace in teaching speaking. A descriptive qualitative research approach was utilized, incorporating observations, interviews, and questionnaires for data collection. The findings revealed that the Speechace has a speaking test program that users can use for free. At the end of the test, there is a transcription of the assessment which contains sections on speaking skills such as vocabulary, grammar, fluency, coherence and relevance. Apart from that, Speechace also provides free conversation practice. Meanwhile, to use the speaking practice feature provided by Speechace, user can select the